Pulling the Thread: Nature and Weaving in the Work of Magda Bolumar and Moisès Villèlia (BSAA arte, 2019)
The union of Magda Bolumar, a painter barely known today, and Moisès Villèlia, reputed informalist sculptor with work in international museums, was undoubtedly one of the most productive and enriching exchanges of Spanish Contemporary art of the 20th century. However, the political and socio-cultural context, as well as the strict canons that still govern the History of Art, makes the figure of Magda remain under the shadow of Moisès. In this study we show that, if we apply the variable of gender in the historical analysis of the life and work of artistic couples like the one discussed here, we should review the traditional historiogaphy to offer a more complete reading, including many women who have been relegated until now.
Keywords: Contemporary Art; Catalan avant-garde; Informalism; couples of artists; feminist art